Auxiliary agent assisted cross-linked silicon-polyolefin interpolymer formation with cross-linking agent
By using a melt blending method of ethylene-SiH polymer, 1,3-dibenzoylpropane and triarylborane, the curing process of cross-linked polyethylene material was controlled, solving the problems of uneven thickness and slow rate in wet curing, and realizing controllable cross-linking and degradable cross-linked polyethylene material.
Patent Information
- Application Number
- CN202380041232.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-22
- Publication Date
- 2024-12-27
AI Technical Summary
Existing technologies for the wet curing of cross-linked polyethylene materials suffer from problems such as uneven material thickness, slow curing rate, and equipment dependence. In particular, there are challenges in the complete curing of thick parts, and traditional methods are difficult to prepare degradable and recyclable cross-linked polyethylene materials.
By employing a melt blending method, using ethylene-SiH polymer, 1,3-dibenzoylpropane as a crosslinking agent, triarylborane and alkylamine inhibitor, and controlling the temperature and component ratio, a controllable crosslinking network is formed to achieve crosslinking of polyethylene-Si polymer.
This method enables controlled curing of cross-linked polyethylene materials, improves the material's processing performance, and makes it biodegradable and recyclable, solving the problems of uneven curing and slow curing rate in traditional methods.
Smart Images

Figure CN119213057A_ABST
Abstract
Description
[0001] Cross-linked polyolefins, such as cross-linked polyethylene, are known to have superior mechanical properties compared to their non-cross-linked counterparts, which results in improved performance in their end-use applications.
[0002] One common method of crosslinking polyolefins requires a processing step to functionalize the polyolefin. The functionalized polyolefin is then subjected to a crosslinking step that requires an initiator such as a peroxide or a condensation catalyst.
[0003] Another common method for curing polyolefin materials (such as polyethylene) is wet curing. Wet curing requires the installation of hydrolyzable functional groups on polyethylene, such as vinyl trimethoxy silane (VTMS), and functionalized polyethylene is exposed to moisture subsequently. However, the curing of such materials requires moisture to penetrate into the material, which limits the curing rate and may cause the uneven curing of the entire material thickness. Meanwhile, wet curing requires specific devices, such as humidity chambers or saunas, usually. The wet curing of polyolefin materials usually occurs in the process of several days or weeks. The dependence of the curing process on water diffusion often causes the uneven curing of the entire material thickness, and makes the complete curing of thick parts challenging.
[0004] In view of the continued growth in the use of cross-linked polyolefins, the art recognizes a continuing need for new methods for cross-linking polyethylene and for forming cross-linked polyethylene that is degradable and / or recyclable. Summary of the invention
[0005] The present disclosure provides a method. In one embodiment, the method includes melt blending a composition at a temperature of 80°C to 200°C, the composition consisting of: (i) an ethylene-SiH polymer, (ii) a crosslinking agent, the crosslinking agent being 1,3-dibenzoylpropane, (iii) a triarylborane, and (iv) an alkylamine inhibitor. The method also includes forming a crosslinked ethylene-Si polymer.
[0006] The present disclosure provides a composition. In one embodiment, the composition comprises a cross-linked ethylene-Si polymer having structure (1)
[0007]
[0008] Applicants have discovered that upon heating, the alkylamine inhibitor decomposes and releases triarylborane as a catalyst to react with the ethylene-SiH polymer and the crosslinker (which is a bifunctional crosslinker) to produce a crosslinked network. In the absence of an alkylamine inhibitor, the crosslinking reaction is uncontrollable, resulting in a loss of processability, which is detrimental to the production of finished parts. The resulting Si-OC bonds may be degradable, making the crosslinked ethylene-Si polymer recyclable. Applicants have further discovered that the temperature at which crosslinking occurs is adjustable based on the characteristics of the alkylamine inhibitor used. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] 1( a) and 1( b) are graphs showing corresponding MDR curves of FIG. 1( a ) where 1,3-DBP and 100 ppm FAB are suppressed by 1.2 equivalents of NEt3 (IE1) and FIG. 1( b ) where 1,3-DBP and 50 ppm FAB are suppressed by 1.2 equivalents of NEt3 (IE2) at different temperatures according to an embodiment of the present disclosure.
[0010] 2 is a graph showing SiH conversion of 1,3-DBP samples containing (i) no FAB, (ii) 100 ppm FAB (IE1) and (iii) 50 ppm FAB (IE2) each inhibited by 1.2 equivalents of NEt3 after 30 minutes at different curing temperatures according to embodiments of the present disclosure. The data point at 100° C. represents the SiH conversion in the as-compounded sample blended at 100° C. for 5 minutes.
[0011] 3 is a graph showing MDR curves of a 1,3-DBP sample containing 100 ppm FAB suppressed by 1.2 equivalents of iPr2NH (IE3) at different temperatures according to an embodiment of the present disclosure.
[0012] Figure 4 is a graph showing the SiH conversion of 1,3-DBP samples containing 100 ppm FAB suppressed by 1.2 equivalents of iPr2NH(IE3) at different temperatures. The data point at 100°C represents the SiH conversion in the as-compounded sample blended at 100°C for 5 minutes.
[0013] 5 is a graph showing MDR curves of a 1,3-DBP sample containing 100 ppm FAB suppressed by 1.2 equivalents of Pr2NH (IE4) at different temperatures according to an embodiment of the present disclosure.
[0014] 6 is a graph showing SiH conversion of 1,3-DBP samples containing 100 ppm FAB suppressed by 1.2 equivalents of Pr2NH (IE4) after 30 minutes at different temperatures according to an embodiment of the present disclosure. The data point at 100° C. represents the SiH conversion in the as-compounded sample blended at 100° C. for 5 minutes.
[0015] 7 is a graph showing MDR curves of 1,3-DBP samples containing 100 ppm FAB suppressed by 1.2 equivalents of tOA (IE5) at different temperatures according to an embodiment of the present disclosure.
[0016] 8 is a graph showing SiH conversion of 1,3-DBP samples containing 100 ppm FAB inhibited by 1.2 equivalents of tOA (IE5) after 30 minutes at different temperatures according to embodiments of the present disclosure. The data point at 100° C. represents the SiH conversion in the as-compounded sample blended at 100° C. for 5 minutes.
[0017] 9( a ) and 9 ( b ) are graphs showing MDR curves of 1,3-DBP samples containing (a) 100 ppm FAB (IE6) and (b) 500 ppm FAB (IE7) each suppressed by 1.2 equivalents of nOA at different temperatures according to embodiments of the present disclosure.
[0018] Figure 10 is a graph showing SiH conversion after 30 minutes at different temperatures for 1,3-DBP samples containing 100 ppm FAB (IE6) and 500 ppm FAB (IE7), each inhibited by 1.2 equivalents of nOA. The data point at 100°C represents the SiH conversion in the as-compounded sample blended at 100°C for 5 minutes.
[0019] 11 is a graph showing the MDR curves of 1,3-DBP samples containing 100 ppm FAB suppressed by 1.2 equivalents of Pip (CS2), TMP (CS4), and DMP (CS3) at 180°C.
[0020] 12 is a graph showing the MDR curves of 1,3-DBP samples containing 100 ppm FAB suppressed by 1.2 equivalents of 2-AH (CS5) at different temperatures.
[0021] definition
[0022] Any reference to the Periodic Table of the Elements is to the Periodic Table as published by CRC Press, Inc., 1990-1991. A group of elements in this table is referred to by a new notation for numbering the groups.
[0023] For purposes of U.S. patent practice, the contents of any referenced patent, patent application, or publication are incorporated by reference in their entirety (or their equivalent U.S. versions are so incorporated by reference), especially with respect to definitions (to the extent not inconsistent with any definitions specifically provided in this disclosure) and common general knowledge in the art.
[0024] Numerical ranges disclosed herein include all values from the lower limit to the upper limit, and include the lower limit and the upper limit. For ranges containing exact values (e.g., 1 or 2, or 3 to 5, or 6, or 7), any sub-range between any two exact values is included (e.g., the above ranges 1 to 7 include 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6, etc.).
[0025] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are based on weight and all test methods are current as of the filing date of this disclosure.
[0026] The term "composition" refers to a mixture of materials comprising the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0027] The terms "comprising", "including", "having" and their derivatives are not intended to exclude the presence of any additional components, steps or procedures, whether or not these components, steps or procedures are specifically disclosed. For the avoidance of any doubt, unless stated to the contrary, all compositions claimed by using the term "comprising" may include any additional additives, adjuvants or compounds, whether in polymeric form or otherwise. In contrast, the term "consisting essentially of excludes any other components, steps or procedures (except those that are not essential to operability) from the scope of any subsequent statements. The term "consisting of" excludes any components, steps or procedures that are not specifically described or listed. Unless otherwise stated, the term "or" refers to the listed members individually and in any combination. The use of the singular includes the use of the plural, and vice versa.
[0028] "Dalton" is a unit of polymer molecular weight, equivalent to the atomic mass unit, abbreviated as "Da" or "kDa" (kilodalton).
[0029] "Ethylene-based polymers" or "ethylene polymers" are polymers that contain a majority amount of polymerized ethylene, based on the weight of the polymer, and optionally may contain at least one comonomer. Ethylene-based polymers typically contain at least 50 mole percent (mol%) units derived from ethylene (based on the total amount of polymerizable monomers).
[0030] A "hydrocarbon" (or "hydrocarbyl" or "hydrocarbyl group") is a compound containing only hydrogen and carbon atoms.
[0031] As used herein, the term "heterohydrocarbon" ("heterohydrocarbon" or "heterohydrocarbon group") and similar terms refer to the corresponding hydrocarbon in which at least one carbon atom is replaced by a heteroatom group (eg, Si, O, N or P).
[0032] The term "substituted hydrocarbon" (or "substituted hydrocarbyl" or "substituted hydrocarbyl group") refers to a hydrocarbon in which one or more hydrogen atoms are independently replaced by a heteroatom group. The term "substituted heterohydrocarbyl" ("substituted heterohydrocarbyl" or "substituted heterohydrocarbyl group") and similar terms as used herein refer to the corresponding heterohydrocarbyl in which one or more hydrogen atoms are independently replaced by a heteroatom group.
[0033] "Interpolymers" are polymers prepared by polymerizing at least two different types of monomers. The generic term interpolymer thus includes copolymers (employed to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.
[0034] "Olefin-based polymers" or "polyolefins" are polymers containing a majority mole % of polymerized olefin monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin-based polymers include ethylene-based polymers and propylene-based polymers. Representative polyolefins include polyethylene, polypropylene, polybutene, polyisoprene, and various interpolymers thereof.
[0035] A "polymer" is a polymeric compound prepared by polymerizing monomers, whether of the same or a different type. The generic term polymer thus encompasses the term "homopolymer" as defined below.
[0036] (used to refer to polymers prepared from only one type of monomer, it being understood that trace impurities may be incorporated into the polymer structure) and the term "interpolymer". Trace impurities (e.g., catalyst residues) may be incorporated into and / or within the polymer. It also encompasses all forms of copolymers, such as random copolymers, block copolymers, and the like. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" refer to copolymers prepared by polymerizing ethylene or propylene and one or more additional polymerizable α-olefin monomers, respectively, as described above. It should be noted that although polymers are often referred to as "made from" one or more specified monomers, "based on" a specified monomer or monomer type, "containing" a specified monomer content, etc., in this context, the term "monomer" is understood to refer to the polymerized residue of the specified monomer rather than unpolymerized material. In general, polymers are referred to herein as "units" based on the polymerized form of the corresponding monomer.
[0037] "Propylene-based polymers" are polymers that contain a majority amount of polymerized propylene, based on the weight of the polymer, and optionally may include at least one comonomer. Propylene-based polymers typically contain at least 50 mole percent (mol%) units derived from propylene (based on the total amount of polymerizable monomers).
[0038] Test Method
[0039] density Measured according to ASTM D792, Method B (g / cc or g / cm 3 ).
[0040] Differential scanning calorimetry (DSC). Differential scanning calorimetry (DSC) is used to measure Tm, Tc, Tg and crystallinity in ethylene-based polymer samples. About 5 mg to 8 mg sample is weighed and placed in a DSC pan. The lid is screwed on the pan to ensure a closed atmosphere. Unless otherwise stated, the sample pan is placed in a DSC unit and then heated to a temperature of 200 ° C at a rate of 10 ° C / min. The sample is kept at this temperature for three minutes. The sample is then cooled to -90 ° C at a rate of 10 ° C / min, and isothermally maintained at this temperature for three minutes. The sample is then heated at a rate of 10 ° C / min until fully melted (second heating). Unless otherwise stated, the melting point (Tm) and glass transition temperature (Tg) of each polymer are determined by the second heating curve. Record the peak heat flow temperature of Tm.
[0041] FTIR-ATR .Infrared spectra were collected on a Perkin ElmerFrontier Fourier transform infrared spectrometer (FT-IR) with an attenuated total reflectance (ATR) attachment (single bounce diamond / ZnSe). The sample was cut with scissors to expose the clean inner surface, then placed in the attachment and kept at a force of about 0.4 at the peak absorbance, and 4-16 scans were collected depending on the quality of the spectrum. Spectra were collected at least in triplicate to ensure representative sampling of the entire sample. SiH conversion rate. The SiH conversion is the mole % of SiH bonds in the ethylene-SiH polymer that are converted to Si-C bonds ("SiC") due to the hydrosilylation reaction by measuring the 2920 cm -1 The peak at 942 cm -1 The SiH conversion was determined by setting the baseline at 887 cm -1 The conversion rate is determined by the Si-H peak at 887 cm -1 Absorbance at 887 cm before hydrosilylation reaction) / ( -1 absorbance at ).
[0042] Gel content Measured according to ASTM D2765-16 by overnight heat extraction with xylene.
[0043] Gel Permeation Chromatography The chromatographic system consisted of a PolymerCharGPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set at 160°C and the column compartment was set at 150°C. The columns were an Agilent PLgel MIXED 7.5×50 mm, 20 μm linear mixed bed guard column followed by four Agilent PLgel MIXED-A 7.5×300 mm, 20 μm linear mixed bed columns. The chromatographic solvent was 1,2,4-trichlorobenzene (TCB) containing 200 ppm of butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume used was 200 microliters and the flow rate was 1.0 ml / min.
[0044] Agilent EasiCal polystyrene standards (EasiCal PS-1 and EasiCal PS-2) were used to calibrate the GPC column set. Each EasiCal system consists of two different scrapers supporting a mixture of 5 polymer standards (approximately 5 mg) to obtain 20 molecular weight points in the range of approximately 580 g / mole to 6,570,000 g / mole. A single scraper was added to a vial covered with a septum, sealed and loaded into the PolymerChar autosampler. 8 mL of solvent was added to each vial using the PolymerChar instrument control software, and the standards were dissolved at 160 ° C for 15 minutes under high-speed shaking before being injected into the chromatography system. The peak molecular weight of the polystyrene standard was converted to a polyethylene molecular weight using equation 1 (as Williams and Ward, Journal of Polymer Science, Polymer Express (J. Polym. Sci., Polym. Let.), 6, 621 (1968)):
[0045] M 聚乙烯 =A×(M 聚苯乙烯 ) B (EQ1), where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.
[0046] A third-order polynomial was used to fit the corresponding polyethylene equivalent calibration points. A small adjustment (approximately 0.375 to 0.445) was made to A to correct for column resolution and band broadening effects so that a linear low density polyethylene standard was obtained at 120,000 Mw. Total plate counts for the GPC column set were performed with decane (3% v / v TCB introduced by a micro pump). Plate counts (Equation 2) and symmetry (Equation 3) were measured at 200 microliter injections according to the following equations:
[0047] wherein RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the maximum height of the peak, and 1 / 2 height is 1 / 2 the height of the peak maximum; and
[0048] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the maximum peak position, tenth height is 1 / 10 the height of the peak maximum, and where post-peak refers to the tail of the peak at a later retention volume than the peak maximum, and where pre-peak refers to the front of the peak at an earlier retention volume than the peak maximum. The plate count of the chromatographic system should be greater than 18,000, and the symmetry should be between 0.98 and 1.22.
[0049] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml and the solvent (containing 200 ppm BHT) was added to the septum-capped vial by the PolymerChar high temperature autosampler. The samples were dissolved at 160°C for two hours under high speed shaking.
[0050] Based on the GPC results, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer, according to equations 4-6, the PolymerChar GPCOne TM The software was used to calculate the Mn value of the baseline-subtracted IR chromatogram at each equidistant data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1. (GPC) 、Mw (GPC) and Mz (GPC) Calculation of. Equation 4-Equation 6 are as follows:
[0051]
[0052] as well as
[0053]
[0054] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (nominal)) for each sample by comparing the RV of the corresponding decane peak in the sample (RV (FM sample)) with the RV of the decane peak in the narrow standard calibration (RV (FM calibrated)). It was then assumed that any changes in the time of the decane marker peak were related to linear changes in the flow rate (flow rate (effective)) for the entire run. In order to promote the highest accuracy of the RV measurement of the flow marker peak, the peak of the flow marker concentration chromatogram was fit to a quadratic equation using a least squares fitting procedure. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated according to Equation 7: Flow rate (effective) = flow rate (nominal) * (RV (FM calibration) / RV (FM sample)) (EQ7). By PolymerChar GPCOne TM The software completes the processing of the flow marker peaks. An acceptable flow rate correction is such that the effective flow rate should be within + / - 0.7% of the nominal flow rate.
[0055] Moving Die Rheometer (MDR). Sample cure evaluation was performed using an Alpha Technologies Advanced Polymer Analyzer (APA 2000) at a specified temperature and 0.5° arc for 30 minutes according to ASTM D5289-12, Standard Test Method for Rubber Properties - Vulcanization Using a Rotorless Curing Apparatus. The test was run at a frequency of 100 cycles per minute (cpm). The lowest measured torque value was designated as "ML" and expressed in deciNewton-meters (dN-m). As the cure or cross-linking progressed, the measured torque values increased and eventually reached a maximum torque value. The maximum or highest measured torque value was designated as "MH" and expressed in dN-m. All other things being equal, the greater the MH torque value, the greater the degree of cross-linking. The T90 cross-linking time was determined as the number of minutes required to reach a torque value equal to 90% of the difference MH minus ML (MH-ML) (i.e., 90% of the distance from ML to MH). The shorter the T90 cross-linking time, i.e., the earlier 90% of the way the torque value changes from ML to MH, the faster the cure rate of the test sample. On the contrary, the longer the T90 crosslinking time, ie the longer the time required for the torque value to reach 90% from ML to MH, the slower the curing speed of the test sample.
[0056] Melt index.The melt index (or "I2") of ethylene-based polymers is measured according to ASTM D-1238 at 190°C / 2.16 kg (melt index I10 at 190°C / 10.0 kg). 10 Calculate I by the ratio of I2 10 / I2. The melt flow rate MFR of the propylene-based polymer is measured according to ASTM D-1238 at 230°C / 2.16kg.
[0057] Nuclear magnetic resonance (NMR) characterization of the terpolymer. for 1 For H NMR experiments, each sample was dissolved in tetrachloroethane-d2 in a 5 mm NMR tube. The concentration was about 100 mg / 1.8 mL. Each tube was then heated in a heating block set at 110 °C. The sample tubes were repeatedly vortexed and heated to obtain a uniformly flowing fluid. The spectra were acquired on a VARIAN 500 MHz spectrometer. 1 HNMR spectroscopy. Standard single pulse 1 H NMR experiments. The following acquisition parameters were used: 60 s relaxation delay, 16-32 scans. All measurements were performed at 110 °C without sample rotation. For the resonance peak of the solvent (residual protonated tetrachloroethane), 1 The H NMR spectrum was located at "5.99 ppm". 1 H NMR is used to determine the polymerized SiH comonomer content (wt%) in ethylene-SiH polymers. "Weight % SiH monomer" is calculated based on the integration of the SiMe proton resonance relative to the integration of the CH2 protons associated with the ethylene unit and the CH3 protons associated with the octene unit. "Weight % octene (or other α-olefin)" can be similarly determined by reference to the CH3 protons associated with the octene unit (or other α-olefin).
[0058] SiH conversion rate. The SiH conversion was determined using FTIR-ATR. See FTIR-ATR Test Methods. The SiH conversion percentage (%) is described under FTIR-ATR Test Methods. DETAILED DESCRIPTION
[0059] The present disclosure provides a method. In one embodiment, the method includes melt blending a composition at a temperature of 80°C to 200°C, the composition consisting of: (i) an ethylene-SiH polymer, (ii) a crosslinking agent, the crosslinking agent being 1,3-dibenzoylpropane, (iii) a triarylborane, and (iv) an alkylamine inhibitor. The method also includes forming a crosslinked ethylene-Si polymer.
[0060] The method comprises melt blending a composition consisting of (i) an ethylene-SiH polymer, (ii) a crosslinking agent, which is 1,3-dibenzoylpropane, (iii) a triarylborane, and (iv) an alkylamine inhibitor at a temperature of 80°C to 200°C. The ethylene-SiH polymer is composed of (1) an ethylene monomer, (2) 0.1 wt% to 3.9 wt% of a SiH comonomer, and (3) an optional C3-C 12 As used herein, "SiH comonomer" (interchangeably referred to as "SiH") is a silane monomer of Formula 1:
[0061] (Formula 1)
[0062] A-(SiBC-O) x -Si-EFH
[0063] wherein A is an alkenyl group,
[0064] B is a hydrocarbon group or hydrogen,
[0065] C is a hydrocarbyl group or hydrogen, and
[0066] wherein B and C may be the same or different, and further B is a hydrocarbyl group, C is a hydrocarbyl group, and further B and C are the same;
[0067] H is hydrogen, and x ≥ 0;
[0068] E is a hydrocarbon group or hydrogen,
[0069] F is a hydrocarbyl group or hydrogen, E and F may be the same or different, and when E is a hydrocarbyl group, F is a hydrocarbyl group, and E and F may be the same hydrocarbyl group. Non-limiting examples of suitable SiH comonomers of Formula 1 include compounds s1) (allyl dimethyl silane), s2) (propylene dimethyl silane), s3) (butenyl dimethyl silane), s4) (hexenyl dimethyl silane), s5) (octenyl dimethyl silane), s6) (decenyl dimethyl silane), s7) norbornenyl ethyl dimethyl silane, s8) octahydrodimethylene naphthyl ethyl dimethyl silane, s9) vinyl tetramethyl disiloxane, s10) allyl tetramethyl disiloxane, s11) -butenyl tetramethyl disiloxane, s12) hexenyl tetramethyl disiloxane, s13) octenyl tetramethyl disiloxane, s14) decenyl tetramethyl disiloxane, s15) norbornenyl ethyl tetramethyl disilane, s16) octahydrodimethylene naphthyl ethyl tetramethyl disiloxane, as follows:
[0070]
[0071] In one embodiment, the SiH comonomer is selected from allyldimethylsilane, hexenyldimethylsilane, octenyldimethylsilane and hexenyltetramethyldisiloxane.
[0072] In one embodiment, the ethylene-SiH polymer is an ethylene / α-olefin / SiH terpolymer. The α-olefin in the ethylene / α-olefin / SiH comonomer terpolymer can be C3-C 12 α-olefin or C4-C8 α-olefin. Non-limiting examples of suitable α-olefins include propylene, butene, hexene, octene and ethylidene norbornene, for ethylene / propylene SiH terpolymer, ethylene / butene / SiH terpolymer, ethylene / hexene / SiH terpolymer, ethylene / octene / SiH terpolymer and ethylene / ethylidene norbornene / SiH terpolymer, respectively.
[0073] In one embodiment, the ethylene / α-olefin / SiH terpolymer is an ethylene / octene / SiH terpolymer. Non-limiting examples of suitable ethylene / octene / SiH terpolymers include ethylene / octene / hexenyldimethylsilane (HDMS) terpolymers, ethylene / octene / octenyldimethylsilane (ODMS) terpolymers, and combinations thereof.
[0074] In one embodiment, the ethylene / α-olefin / SiH terpolymer is an ethylene / octene / SiH terpolymer. The ethylene / octene / SiH terpolymer comprises 30 wt% to 41 wt% octene and 0.5 wt% to 5 wt% or 1.0 wt% to 3.5 wt% SiH comonomer, and has a density of 0.87 g / cc to 0.89 g / cc and a MI of 1 g / 10min to 18 g / 10min or 2 g / 10min to 12 g / 10min. Non-limiting examples of suitable ethylene / octene / SiH terpolymers include ethylene / octene / allyl dimethyl silane (ADMS) terpolymers, ethylene / octene / hexenyl dimethyl silane (HDMS) terpolymers, and ethylene / octene / octenyl dimethyl silane (ODMS) terpolymers.
[0075] In one embodiment, the ethylene-SiH polymer is ethylene / octene / hexenyldimethylsilane.
[0076] In one embodiment, the ethylene-SiH polymer is an ethylene / octene / ODMS terpolymer.
[0077] The composition comprises a crosslinking agent, which is 1,3-dibenzoylpropane.
[0078] The composition comprises triarylborane. The three aryl groups of triarylborane can be the same or different. Each of the three aryl groups can independently include one, or two, or three, or four, or five substituents selected from hydrogen, chlorine, fluorine, trifluoromethyl groups and combinations thereof. Triarylborane is a Lewis acid catalyst and promotes the hydrosilylation reaction between the SiH monomer of the ethylene-SiH polymer and the carbonyl group of 1,3-dibenzoylpropane. Non-limiting examples of suitable triarylboranes include tris(pentafluorophenyl)borane (FAB), tris(3,5-bis(trifluoromethyl)phenyl)borane; bis(3,5-bis(trifluoromethyl)phenyl)(2,4,6-trifluorophenyl)borane; bis(3,5-bis(trifluoromethyl)phenyl)(2,5-bis(trifluoromethyl)phenyl)borane; bis(3,5-bis(trifluoromethyl)phenyl)(4-trifluoromethylphenyl)borane, bis(3,5-bis(trifluoromethyl)phenyl)(2,6-difluorophenyl)borane, tris(2,5-bis(trifluoromethyl)phenyl)borane, and combinations thereof.
[0079] The composition comprises an alkylamine inhibitor. The alkylamine inhibitor is a C2-C 16 Alkylamine or C3-C 12 Alkylamine. The alkylamine inhibitor can be a linear alkylamine, a branched alkylamine or a cyclic alkylamine structure. The alkylamine inhibitor binds to the borane catalyst and prevents the borane catalyst from interacting with Si-H, thereby rendering the borane catalytically inactive. Upon heating, the amine-borane complex decomposes and releases free borane that is capable of catalyzing the reaction. Suitable C2-C 16 Non-limiting examples of alkylamine inhibitors include triethylamine, diisopropylamine, di-n-propylamine, tert-octylamine, n-octylamine, 2-amino-2,4,4-trimethylpentane, 2-aminoheptane, piperidine, 2,6-dimethylpiperidine, 2,2,6,6-tetramethylpiperidine, and combinations thereof.
[0080] (i) ethylene-SiH polymer, (ii) crosslinking agent which is 1,3-dibenzoylpropane, (iii) triarylborane and (iv) alkylamine inhibitor are melt blended or otherwise mixed at a temperature and for a period of time sufficient to make the mixture completely homogenous. Melt blending is carried out at a temperature of 80°C to 200°C, or 90°C to 150°C, or 100°C to 120°C for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes by intermittent mixing or continuous mixing. In the presence of triarylborane catalyst, melt blending initiates a hydrosilylation reaction between Si-H moieties of ethylene-SiH polymer and carbonyl groups of 1,3-dibenzoylpropane, thereby bonding polymer chains of ethylene-SiH polymer with 1,3-dibenzoylpropane bonds or otherwise crosslinking to form a crosslinked ethylene-Si polymer. The alkylamine inhibitor binds to the borane catalyst and prevents the borane catalyst from interacting with Si-H, thereby rendering the borane catalytically inactive. Upon heating, the amine-borane complex decomposes and releases free borane that is capable of catalyzing the reaction. As used herein, "crosslinked ethylene-Si polymer" is the reaction product between an ethylene-SiH polymer and 1-3-dibenzoylpropane, whereby Si-OC bonds crosslink or bond the individual chains of the ethylene-SiH polymer to each other.
[0081] In one embodiment, the crosslinked ethylene-Si polymer is a reaction product between an ethylene-SiH polymer and 1-3-dibenzoylpropane, whereby structure (1) is a bond that crosslinks or bonds the individual chains of the ethylene-SiH polymer to each other:
[0082] Structure (1)
[0083]
[0084] In one embodiment, the crosslinked ethylene-Si polymer comprises bonds of structure (1) to form a crosslinked polymer network having the following structure (2)
[0085] Structure (2)
[0086]
[0087] The term "polymer" in structure (2) refers to individual chains of ethylene-SiH polymers.
[0088] In one embodiment, melt blending is performed by batch mixing in a batch mixer. (i) ethylene-SiH polymer, (ii) crosslinking agent being 1,3-dibenzoylpropane, (iii) triarylborane and (iv) alkylamine inhibitor are added to a batch mixer and melt blended or otherwise mixed at a temperature of 80°C to 200°C, or 90°C to 150°C, or 100°C to 120°C for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes. Non-limiting examples of suitable batch mixers include BANBURY TM Mixer, BOLLING TM Mixer or HAAKE TM Mixer. Batch mixing to form a cross-linked ethylene-Si polymer having structure (1) and / or structure (2).
[0089] In one embodiment, melt blending is performed by continuous mixing in an extruder. (i) ethylene-SiH polymer, (ii) a crosslinking agent that is 1,3-dibenzoylpropane, (iii) triarylborane, and (iv) an alkylamine inhibitor are introduced into an extruder and melt blended or otherwise mixed at a temperature of 80°C to 200°C, or 90°C to 150°C, or 100°C to 120°C for 1 minute to 20 minutes, or 2 minutes to 15 minutes, or 3 minutes to 10 minutes to form a uniform composition. The extruder can be a continuous single screw extruder or a continuous twin screw extruder. Non-limiting examples of suitable extruders include FARREL TM Continuous mixer, COPERION TM Twin screw extruder or BUSS TM Kneading continuous extruder. The homogeneous composition leaves the outlet die of the extruder as an extrudate, which is a functionalized ethylene-Si polymer having structure (1) and / or structure (2).
[0090] In one embodiment, the method includes a composition consisting of: (i) an ethylene-SiH polymer, (ii) a crosslinker, which is 1,3-dibenzoylpropane, (iii) a triarylborane, and (iv) an alkylamine inhibitor. The ethylene-SiH polymer contains Si atoms present in the SiH comonomer. 1,3-dibenzoylpropane contains a carbonyl moiety. As used herein, "Si: carbonyl molar ratio" is the ratio of the molar number of Si atoms in the ethylene-SiH polymer to the molar number of carbonyl groups in 1,3-dibenzoylpropane. The method includes providing a composition having components (i)-(iv) and a Si: carbonyl molar ratio of 0.75:1 to 1:1 to 1.25:1, and melt blending the composition at a temperature of 80°C to 200°C and forming a crosslinked ethylene-Si polymer. The crosslinked ethylene-Si polymer has structure (1) and / or structure (2).
[0091] In one embodiment, the method includes a composition consisting of: (i) ethylene-SiH polymer, (ii) a crosslinker, which is 1,3-dibenzoylpropane, (iii) triarylborane and (iv) an alkylamine inhibitor. As used herein, "alkylamine: triarylborane molar ratio" is the ratio of the number of moles of alkylamine inhibitor to the number of moles of triarylborane in the composition. The method includes providing a composition having components (i)-(iv) with an alkylamine: triarylborane ratio of 1:1 to 2:1 (alone, or in combination with a composition having components (i)-(iv) and a Si: carbonyl molar ratio of 0.75:1 to 1:1 to 1.25:1 (Si: carbonyl molar ratio 1.0+ / -0.25)), melt blending the composition at a temperature of 80°C to 200°C and forming a crosslinked ethylene-Si polymer. The crosslinked ethylene-Si polymer has structure (1) and / or structure (2).
[0092] In one embodiment, the method comprises melt blending a composition consisting of (i) 93 wt % to 98 wt % ethylene / α-olefin / -SiH terpolymer, (ii) 1 wt % to 10 wt % or 3 wt % to 8 wt % of a crosslinking agent (which is 1,3-dibenzoylpropane), (iii) 5 ppm to 5000 ppm, or 50 ppm to 500 ppm of trialkylborane and (iv) 5 ppm-500 ppm, or 10 ppm to 200 ppm of alkylamine, and the composition has a Si: carbonyl molar ratio of 0.75:1 to 1:1 to 1.25:1 (Si: carbonyl molar ratio 1.0 + / - 0.25) and an alkylamine: triarylborane ratio of 1:1 to 2:1. The weight percentages are based on the total weight of the composition. The method also includes forming a crosslinked ethylene-Si polymer. The crosslinked ethylene-Si polymer has structure (1) and / or structure (2).
[0093] The present disclosure provides a composition. In one embodiment, the composition comprises a cross-linked ethylene-Si polymer having structure (1)
[0094] Structure (1)
[0095]
[0096] The crosslinked ethylene-Si polymer having structure (1) has one, some or all of the following characteristics:
[0097] (i) a density of 0.86 g / cc to 0.88 g / cc, and / or
[0098] (ii)M H -M L 1 dN*m to 3.5 dN*m, and / or
[0099] (iii) 3500 ppm to 5100 ppm silicon atoms, and / or
[0100] (iv) 1 ppm to 10 ppm of boron atoms.
[0101] In one embodiment, the composition comprises a crosslinked ethylene-Si polymer having structure (2)
[0102] Structure (2)
[0103]
[0104] The term "polymer" in structure (2) refers to individual chains of ethylene-SiH polymers.
[0105] Applicants have discovered that upon heating, the alkylamine inhibitor decomposes and releases triarylborane as a catalyst to react with the ethylene-SiH polymer and the crosslinking agent (which is a bifunctional crosslinking agent) to produce a crosslinked network. In the absence of an alkylamine inhibitor, the crosslinking reaction is uncontrollable, resulting in a loss of processability, which is detrimental to the production of finished parts. Applicants have further discovered that the temperature at which crosslinking occurs is adjustable based on the type of alkylamine inhibitor used.
[0106] By way of example and not limitation, some embodiments of the present disclosure will now be described in detail in the following examples.
[0107] Example
[0108] A. Synthesis and Properties of Polymers P1, P2, and P3
[0109] The ethylene / octene / silane copolymerization of the polymer (ethylene-SiH polymer) was carried out in a batch reactor designed for ethylene homopolymerization and copolymerization. The reactor was equipped with an electric heating band and an internal cooling coil containing cooling glycol. Both the reactor and the heating / cooling system were controlled and monitored by a process computer. The bottom of the reactor was equipped with a dump valve, which emptied the reactor contents into a dump pot connected to the atmosphere. All chemicals and catalyst solutions used for polymerization passed through a purification column before use. ISOPAR-E, 1-octene, ethylene and silane monomers also passed through the column. Ultra-high purity grades of nitrogen (Airgas) and hydrogen (Airgas) were used. The catalyst mixture was prepared by mixing a scavenger (MMAO), an activator (bis(hydrogenated tallow alkyl) methylamine tetra(pentafluorophenyl) borate (1<->)) and a catalyst with an appropriate amount of toluene in an inert glove box to obtain a solution of the desired molar concentration. The solution was then diluted with ISOPAR-E or toluene to achieve the amount required for polymerization and aspirated into a syringe to transfer to a catalyst injection tank.
[0110] In a typical polymerization, ISOPAR-E and 1-octene are loaded into the reactor via separate flow meters. The silane monomer is then added via an injection tank input through an adjacent glove box. After the addition of solvent / comonomer, hydrogen is added (if necessary) while the reactor is heated to a polymerization set point of 120°C. Ethylene is then added to the reactor via a flow meter at the desired reaction temperature to maintain a predetermined reaction pressure set point. The catalyst solution is transferred to an injection tank via a syringe and then added to the reactor via a high pressure nitrogen stream after the reactor pressure set point is reached. The run timer is started upon injection of the catalyst, after which an exotherm and a decrease in reactor pressure are observed to indicate a successful run.
[0111] Ethylene was then added using a pressure controller to maintain the reaction pressure set point in the reactor. The polymerization was run for a set time or until ethylene was absorbed, after which the agitator was stopped and the bottom dump valve was opened to empty the reactor contents into a dump tank. The tank contents were poured into a tray placed in a fume hood and the solvent was allowed to evaporate overnight. The tray containing the remaining polymer was then transferred to a vacuum oven and heated to 100°C under reduced pressure to remove any residual solvent. After cooling to ambient temperature, the polymer was weighed to obtain the yield / efficiency, transferred to a container for storage and submitted for analytical testing.
[0112] Table 1A
[0113] Silane monomer (weight %) Polymer 1 2.17 Polymer 2 2.64 Polymer 3 3.09
[0114] Table 1B: Polymerization conditions for producing ethylene-SiH polymers
[0115]
[0116] Table 1C: Polymer properties (conventional GPC)
[0117]
[0118] *Mole % silane and octene are based on the total moles of monomers in the polymer and are determined by 1H NMR **Silane weight % is calculated by mole % and is based on the weight of the interpolymer.
[0119] *** Bulk polymers from different reactor runs were blended to make Polymer 1 - Polymer 3. The weight % of the components in the blend are given here
[0120] Table 1D: Catalysts and co-catalysts
[0121]
[0122] 1. Materials
[0123] The materials used in the comparative samples (CS) and the inventive examples (IE) are provided in Table 2 below.
[0124] Table 2 - Materials
[0125]
[0126]
[0127] B. Melt Blending
[0128] At 100° C., solutions of (i) ethylene-SiH polymer, (ii) 1,3-dibenzoylpropane (1,3-DBP), and (iii-iv) FAB-alkylamine inhibitor in toluene were fed sequentially into a torque rheometer (Haake PolyLab QC, Thermo Fisher Scientific) equipped with a 20 mL bowl and a two-roll rotor. After adding each component, the sample was mixed at 60 rpm for 1 minute. The final blend was mixed for an additional 4 minutes (t mix =4+1=5 minutes). The hot melt was then taken out of the blender and prepared for further MDR testing.
[0129] The amounts and ratios of components (i)-(iv) in the resulting formulations are provided in Table 3 below.
[0130]
[0131] Table 4
[0132]
[0133] Figure 1(a) and Figure 1(b). MDR curves of 1,3-DBP samples containing 100 ppm FAB (IE1) in Figure 1(a) and 50 ppm FAB (IE2) in Figure 1(b) at different temperatures, each sample was inhibited by 1.2 equivalents of NEt3. Both samples were compounded at 100°C for 5 minutes.
[0134] Figure 1(a) shows the curing curves of the NEt3-inhibited samples containing 100 ppm FAB (IE1) at different temperatures. L ) decreases with increasing curing temperature, and a larger torque increase (M) is recorded at lower curing temperatures. H -M L ).
[0135] In Figure 1(b), reducing the FAB loading to 50 ppm (IE2) significantly reduces the M at a specific temperature compared to the sample in Figure 1(a) containing 100 ppm FAB. L , which reflects the lower level of curing that occurs during the compounding step. Overall, the M H -M L The same temperature dependence is shown as that of the 100 ppm FAB-NEt3 sample. At 150°C and 180°C, the curing time of the 50 ppm FAB-NEt3 sample (Figure 1(b)) is similar to that of the 100 ppm FAB-NEt3 sample (Figure 1(a)). At the same time, the MH -M L is smaller at each temperature, probably because less catalyst is available for the curing reaction under these conditions. Interestingly, at 120°C, the torque increase in 30 minutes for the 50 ppm FAB-NEt3 sample (Figure 1(b)) is greater than that for the 100 ppm FAB-NEt3 sample (Figure 1(a)), and the curing reaction shows no signs of completion.
[0136] As shown in Figures 1(a) and 1(b), one embodiment of the method includes melt blending a composition at a temperature of 120°C to 180°C or 120°C, the composition consisting of: (i) an ethylene / octene / ODMS terpolymer, (ii) a crosslinking agent, the crosslinking agent being 1,3-dibenzoylpropane, (iii) 100 ppm to 50 ppm tris(pentafluorophenyl)borane, (iv) 12 ppm to 24 ppm triethylamine, and forming M H -M L The method comprises forming a cross-linked ethylene-Si polymer of 1 dN*m to 3 dN*m when the composition contains 100 ppm FAB and 24 ppm triethylamine and is melt-blended at a temperature of 120°C. H -M L The method comprises forming a cross-linked ethylene-Si polymer of 1dN*m when the composition contains 50ppm FAB and 12ppm triethylamine and is melt blended at a temperature of 120°C. H -M L A cross-linked ethylene-Si polymer of 3dN*m.
[0137] Figure 2. SiH conversion inhibition by 1.2 equivalents of NEt3 for 1,3-DBP samples without FAB, with 100 ppm FAB (IE1) and with 50 ppm FAB (IE2) after 30 minutes at different curing temperatures.
[0138] The data point at 100°C represents the SiH conversion in the as-compounded sample that was blended at 100°C for 5 minutes. Figure 2 shows that the SiH conversion of FAB-NEt3 samples IE1 and IE2 is the greatest when they are cured at 120°C, further confirming the observed M conversion of FAB-NEt3 samples at different temperatures. H -M L The difference is mainly due to differences in the level of curing.
[0139] Figures 3-4. MDR curves of 1,3-DBP samples containing 100 ppm FAB suppressed by 1.2 equivalents of iPr2NH(IE3) at different temperatures. Figure 4. SiH conversion of 1,3-DBP samples containing 100 ppm FAB suppressed by 1.2 equivalents of iPr2NH(IE3) at different temperatures. The data point at 100°C represents the SiH conversion in the as-compounded sample blended at 100°C for 5 minutes. MDR curves of FAB-iPr2NH samples L Compared with the FAB-Pr2NH sample, the M of the FAB-iPr2NH sample increased significantly (Figure 3). H -M L Both the final SiH conversion rate (Fig. 4) and the final SiH conversion rate (Fig. 5) are higher than those of the FAB-Pr2NH sample.
[0140] As shown in Figures 3 and 4, iPr2NH can be prepared from M in the melt blending temperature range of 120°C to 180°C. H -M L 1dN*m solidified to M H -M L An effective inhibitor of 3dN*m, exhibiting latent cure for all temperatures 120°C-180°C, with 120°C providing the highest cure. One embodiment of the method comprises melt blending a composition consisting of (i) an ethylene / octene / ODMS terpolymer, (ii) a crosslinker, which is 1,3-dibenzoylpropane, (iii) 100 ppm tris(pentafluorophenyl)borane and (iv) 24 ppm diisopropylamine, and forming M H -M L The method comprises forming a cross-linked ethylene-Si polymer of 1 dN*m to 3 dN*m when the composition contains 100 ppm FAB and 24 ppm diisopropylamine and is melt-blended at a temperature of 180°C. H -M L The method comprises forming M when the composition contains 100 ppm FAB and 24 ppm diisopropylamine and is melt-blended at a temperature of 150°C. H -M L The method comprises forming a cross-linked ethylene-Si polymer of 2dN*m when the composition contains 100 ppm FAB and 24 ppm diisopropylamine and is melt-blended at a temperature of 120°C. H -M L A cross-linked ethylene-Si polymer of 3dN*m.
[0141] Figure 5. MDR curves of 1,3-DBP samples containing 100 ppm FAB inhibited by 1.2 equivalents of Pr2NH at different temperatures. Figure 6. SiH conversion of 1,3-DBP samples containing 100 ppm FAB inhibited by 1.2 equivalents of Pr2NH at different temperatures after 30 minutes. The data point at 100°C represents the SiH conversion in the as-compounded sample blended at 100°C for 5 minutes. As shown in Figures 5 and 6, the Pr2NH inhibited sample (IE4) shows the same cure curve and temperature dependence of SiH conversion as the FAB-NEt3 samples (IE1-IE2). The MDR curves of the samples are shown in Figures 5 and 6. L The results show that the FAB inhibition provided by Pr2NH is stronger than that provided by NEt3, and the torque increase is significantly higher than that of the FAB-NEt3 sample, especially at 150°C and 180°C. One embodiment of the method includes melt blending a composition at a temperature of 180°C, the composition consisting of: (i) an ethylene / octene / ODMS terpolymer, (ii) a crosslinker, the crosslinker being 1,3-dibenzoylpropane, (iii) 100 ppm tris(pentafluorophenyl)borane and (iv) 24 ppm diisopropylamine, and forming M H -M L The method comprises forming a cross-linked ethylene-Si polymer of 0.5 dN*m when the composition contains 100 ppm FAB and 24 ppm diisopropylamine and is melt blended at a temperature of 150°C. H -M L The method comprises forming a cross-linked ethylene-Si polymer of 1.5 dN*m when the composition contains 100 ppm FAB and 24 ppm diisopropylamine and is melt-blended at a temperature of 120°C. H -M L A cross-linked ethylene-Si polymer of 3.0 dN*m.
[0142] Figure 7. MDR curves of 1,3-DBP samples containing 100 ppm FAB inhibited by 1.2 equivalents of tOA (IE5) at different temperatures. Figure 8. SiH conversion of 1,3-DBP samples containing 100 ppm FAB inhibited by 1.2 equivalents of tOA (IE5) at different temperatures after 30 minutes. The data point at 100°C represents the SiH conversion in the as-compounded sample blended at 100°C for 5 minutes. At 100 ppm FAB-tOA loading, the MDR curves of the samples are shown in Figure 8. L Lower, and M H -M L It is higher than the 100 ppm FAB-NEt3 and 100 ppm FAB-iPr2NH samples, and higher than the 100 ppm FAB-Pr2NH sample (Figure 7). H-M L and SiH conversion rate decreases with increasing curing temperature (Figure 8). One embodiment of the method includes melt blending a composition consisting of (i) an ethylene / octene / ODMS terpolymer, (ii) a crosslinker, which is 1,3-dibenzoylpropane, (iii) 100 ppm tris(pentafluorophenyl)borane and (iv) 30 ppm tert-octylamine, and forming M H -M L The method comprises forming a cross-linked ethylene-Si polymer of 1.5 dN*m to 3.5 dN*m when the composition contains 100 ppm FAB and 30 ppm tert-octylamine and is melt-blended at a temperature of 180°C. H -M L The method comprises forming a cross-linked ethylene-Si polymer of 1.5 dN*m when the composition contains 100 ppm FAB and 30 ppm tert-octylamine and is melt blended at a temperature of 150°C. H -M L The method comprises forming a cross-linked ethylene-Si polymer of 2.5 dN*m when the composition contains 100 ppm FAB and 30 ppm tert-octylamine and is melt blended at a temperature of 120°C. H -M L A cross-linked ethylene-Si polymer of 3.5 dN*m.
[0143] Figure 9. MDR curves of 1,3-DBP samples containing 100 ppm FAB (IE6) in Figure 9 (a) and 500 ppm FAB (IE7) in Figure 9 (b) suppressed by 1.2 equivalents of nOA at different temperatures. L The sample is shown to have almost no cure during the compounding step (Fig. 9(a)), indicating strong FAB inhibition. Accordingly, the curing kinetics of the nOA-inhibited sample are relatively slow: the sample undergoes minimal thermal curing under the test conditions (30 minutes at 120°C-180°C). Fig. 9(b) shows the curing curve of the 500ppm FAB-nOA sample, which shows that there is almost no additional sample curing during the compounding step compared to the case of 100ppm FAB-nOA. The curing reaction is almost complete within 30 minutes at 200°C. It is noteworthy that the curing rate increases with temperature, and the curing level (M H -M L ) increases accordingly. IR results also show that SiH conversion increases with curing temperature (Figure 10).
[0144] One embodiment of the method comprises melt blending at a temperature of 120°C to 200°C a composition consisting of: (i) an ethylene / octene / ODMS terpolymer, (ii) a crosslinker which is 1,3-dibenzoylpropane, (iii) 100 ppm tris(pentafluorophenyl)borane and (iv) 30 ppm n-octylamine, and forming M H -M L The method comprises forming a cross-linked ethylene-Si polymer of 1.5 dN*m to 3.0 dN*m when the composition contains 100 ppm FAB and 30 ppm n-octylamine and is melt-blended at a temperature of 180°C. H -M L The method comprises forming a cross-linked ethylene-Si polymer of 1.5 dN*m when the composition contains 100 ppm FAB and 30 ppm n-octylamine and is melt blended at a temperature of 150°C. H -M L The method comprises forming a cross-linked ethylene-Si polymer of 1.5 dN*m when the composition contains 100 ppm FAB and 30 ppm n-octylamine and is melt-blended at a temperature of 200°C. H -M L A cross-linked ethylene-Si polymer of 3.0 dN*m.
[0145] Figure 11. MDR curves of 1,3-DBP samples containing 100 ppm FAB inhibited by 1.2 equivalents of Pip (CS2), TMP (CS4), and DMP (CS3) at 180°C. When piperidine (Pip), 2,6-dimethylpiperidine (DMP), and 2,2,6,6-tetramethylpiperidine (TMP) were used as FAB inhibitors, no thermal curing was observed at all, as indicated by the very low MDR curves. L and zero torque increase as shown in (Figure 11).
[0146] Figure 12. MDR curves of 1,3-DBP samples containing 100 ppm FAB inhibited by 1.2 equivalents of 2-AH (CS5) at different temperatures. When 2-AH was used as the FAB inhibitor, no curing occurred when the samples were heated at 120°C and 180°C for 30 minutes.
[0147] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.
Claims
1. A method, comprising: melt blending a composition at a temperature of 80°C to 200°C, the composition comprising (i) ethylene-SiH polymer, (ii) a cross-linking agent, wherein the cross-linking agent is 1,3-dibenzoylpropane, (iii) triarylboranes, and (iv) alkylamine inhibitors; and A cross-linked ethylene-Si polymer is formed.
2. The method according to claim 1, comprising: Compositions having a Si:carbonyl molar ratio of 0.75:1 to 1:1 to 1.25:1 are provided.
3. The method according to any one of claims 1 to 2, comprising Compositions having an alkylamine:triarylborane molar ratio of 1:1 to 2:1 are provided.
4. The method according to any one of claims 1 to 3, comprising A composition is provided, comprising (i) 90 to 99 wt. % of an ethylene / α-olefin / -SiH terpolymer, (ii) 1 to 10 wt% of the crosslinking agent, the crosslinking agent being 1,3-dibenzoylpropane, (iii) 5 ppm to 5000 ppm of said triarylborane, and (iv) 5 ppm to 500 ppm of the alkylamine, wherein the molar equivalent of the alkylamine:borane is from 1:1 to 2:1; and A cross-linked ethylene-Si polymer is formed.
5. The method according to any one of claims 1 to 4, comprising A cross-linked ethylene-Si polymer having Si-OC bonds is formed.
6. The method according to any one of claims 1 to 5, comprising Forming a cross-linked ethylene-Si polymer having structure (1) Structure (1) 7. The method according to any one of claims 1 to 6, comprising melt blending a composition at a temperature of 120°C, the composition comprising (i) ethylene / octene / ODMS terpolymer, (ii) a cross-linking agent, wherein the cross-linking agent is 1,3-dibenzoylpropane, (iii) 100 ppm to 50 ppm tris(pentafluorophenyl)borane, (iv) 12 ppm to 24 ppm triethylamine; and Formation M H -M L A cross-linked ethylene-Si polymer of 1 dN*m to 3 dN*m.
8. The method according to any one of claims 1 to 6, comprising melt blending a composition at a temperature of 120°C to 180°C, the composition comprising (i) ethylene / octene / ODMS terpolymer, (ii) a cross-linking agent, wherein the cross-linking agent is 1,3-dibenzoylpropane, (iii) 100 ppm tris(pentafluorophenyl)borane, (iv) 24 ppm diisopropylamine; and Formation M H -M L A cross-linked ethylene-Si polymer of 1 dN*m to 3 dN*m.
9. The method according to any one of claims 1 to 6, comprising melt blending a composition at a temperature of 120°C to 180°C, the composition comprising (i) ethylene / octene / ODMS terpolymer, (ii) a cross-linking agent, wherein the cross-linking agent is 1,3-dibenzoylpropane, (iii) 100 ppm tris(pentafluorophenyl)borane, (iv) 30 ppm tert-octylamine; and Formation M H -M L A cross-linked ethylene-Si polymer with a range of 1.5 dN*m to 3.5 dN*m.
10. The method according to any one of claims 1 to 6, comprising melt blending a composition at a temperature of 120°C to 200°C, the composition comprising (i) ethylene / octene / ODMS terpolymer, (ii) a cross-linking agent, wherein the cross-linking agent is 1,3-dibenzoylpropane, (iii) 100 ppm tris(pentafluorophenyl)borane, (iv) 30 ppm n-octylamine; and Formation M H -M L A cross-linked ethylene-Si polymer with a range of 1.5 dN*m to 3.0 dN*m.
11. A composition comprising: Crosslinked ethylene-Si polymer having structure (1) Structure (1) 12. The composition of claim 12, having a density of 0.86 g / cc to 0.88 g / cc.
13. The composition according to any one of claims 12 to 13, wherein the M of the composition H -M L 1dN*m to 5dN*m.
14. The composition according to any one of claims 12 to 14, comprising 1000 ppm to 6000 ppm of silicon atoms.
15. The composition according to any one of claims 12 to 15, comprising 0.1 ppm to 100 ppm of boron atoms.
16. The composition according to any one of claims 12 to 16, wherein the crosslinked ethylene-Si polymer has structure (2)
